2015
DOI: 10.1007/s11948-015-9666-9
|View full text |Cite
|
Sign up to set email alerts
|

Human Embryonic Stem Cell Research: Ethical Views of Buddhist, Hindu and Catholic Leaders in Malaysia

Abstract: Embryonic Stem Cell Research (ESCR) raises ethical issues. In the process of research, embryos may be destroyed and, to some, such an act entails the 'killing of human life'. Past studies have sought the views of scientists and the general public on the ethics of ESCR. This study, however, explores multi-faith ethical viewpoints, in particular, those of Buddhists, Hindus and Catholics in Malaysia, on ESCR. Responses were gathered via semi-structured, face-to-face interviews. Three main ethical quandaries emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…While some may know the purpose of HSC donation, they would still be concerned about whether the overall idea of HSC donation is against their religious beliefs or personal ethical views. The interviews with Buddhist, Hindu and Catholic leaders in Malaysia regarding their ethical views towards human embryonic stem cell research revealed contrasting ethical views among them [25]. Although the ongoing de- a Variables with p value <0.200 in univariate analysis were included into the multivariate model using enter method.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…While some may know the purpose of HSC donation, they would still be concerned about whether the overall idea of HSC donation is against their religious beliefs or personal ethical views. The interviews with Buddhist, Hindu and Catholic leaders in Malaysia regarding their ethical views towards human embryonic stem cell research revealed contrasting ethical views among them [25]. Although the ongoing de- a Variables with p value <0.200 in univariate analysis were included into the multivariate model using enter method.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Emerging studies have suggested that stem cell‐based therapies may be a new intervention for neurodegenerative diseases . The success of stem cell therapy may largely depend on high‐efficient supply of desired functional cell types . However, the limited supply of required stem cells, low‐efficient conversion technologies, unstable genetic manipulation, and complex ethical controversies are the main challenges in the field .…”
Section: Introductionmentioning
confidence: 99%
“…The different standpoints reflected different views on the moral value of the embryo, and whether the benefit is more important than the harm. They also found different reflections from leaders from the same religion, expect the Catholic leaders, who repeated the same message as formulated by the Vatican [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The respondents were most positive about donation for treatment with embryonic stem cells (73.6%), while 63.8% would donate to heterosexual couples for reproductive purposes, and 45.1% to single women [ 16 ], indicating that the purpose of donation matters for people’s attitudes. The source of the embryo, either being surplus of created for research purpose, also matters for peoples attitude for usage [ 17 ]. In a qualitative study from 2022 with members of the Swedish general population, the participants had a positive attitude toward using embryonic stem cells to treat PD; however, they raised several conditions under which the treatment should be allowed [ 18 ].…”
Section: Introductionmentioning
confidence: 99%